Comprehensive flood risk management : research for policy and practice : proceedings of the 2nd European Conference on Flood risk management, Floodrisk 2012, Rotterdam, the Nederlands, 19-23 november 2012 /: research for policy and practice : proceedings of the 2nd European Conference on Flood risk management, Floodrisk 2012, Rotterdam, the Nederlands, 19-23 november 2012. (©2013) - Unknown
No abstract available